2019
DOI: 10.1016/j.ecolind.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Taxon-specific variation in δ13C and δ15N of subfossil invertebrate remains: Insights into historical trophodynamics in lake food-webs

Abstract: Keywords: stable isotopes, invertebrate subfossils, sedimentary organic matter, energy and nutrient pathways, boreal lakes Declarations of interest: none 3 4 5 6 7 2 Abstract 8 Carbon and nitrogen stable isotope ratios of sub-fossil invertebrate remains are 9 potentially powerful indicators of nutrient flux, habitat-specific resource utilization, and trophic 10 interactions in lentic food webs, but are rarely estimated for multiple species within lakes. Here 11 we examined historical time series of δ 13 C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…However, because any impact on the δ 15 N of aquatic nitrogen pools at the base of a food web (i.e., in various pools of dissolved inorganic nitrogen [DIN]) is passed up the trophic ladder to producers (phytoplankton) and their consumers (invertebrates and fish), isotopic analyses of tissues from aquatic producers and consumers can also serve as a highly integrative indicator for anthropogenic impacts on nutrient dynamics, in addition to food web structure, in aquatic environments (Hoffman et al 2012;Morrissey et al 2013). While a majority of isotopic research has approached the question of changing freshwater nutrient dynamics through analyses of sedimentary organic matter (e.g., Talbot 2001;Dubois et al 2018), a growing number of studies are demonstrating that δ 15 N compositions of invertebrates and fish can provide a highly sensitive record for environmental change (e.g., Perga et al 2010;Lumb and Johnson 2012;Fera et al 2017;Anas et al 2019).…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because any impact on the δ 15 N of aquatic nitrogen pools at the base of a food web (i.e., in various pools of dissolved inorganic nitrogen [DIN]) is passed up the trophic ladder to producers (phytoplankton) and their consumers (invertebrates and fish), isotopic analyses of tissues from aquatic producers and consumers can also serve as a highly integrative indicator for anthropogenic impacts on nutrient dynamics, in addition to food web structure, in aquatic environments (Hoffman et al 2012;Morrissey et al 2013). While a majority of isotopic research has approached the question of changing freshwater nutrient dynamics through analyses of sedimentary organic matter (e.g., Talbot 2001;Dubois et al 2018), a growing number of studies are demonstrating that δ 15 N compositions of invertebrates and fish can provide a highly sensitive record for environmental change (e.g., Perga et al 2010;Lumb and Johnson 2012;Fera et al 2017;Anas et al 2019).…”
Section: Contextmentioning
confidence: 99%
“…For conservation and restoration efforts in freshwater ecosystems where cultural eutrophication caused by increased nutrient loading poses one of the most significant threats globally (Smith and Schindler 2009), long-term retrospectives that document when and how human activities first began to alter natural ecosystem processes, and the nitrogen cycle in particular, could provide a valuable framework for evaluating which modern human activities pose the greatest risks (Humphries and Winemiller 2009;Canfield et al 2010). Paleolimnological proxy indicators based on the physical, biological, chemical, and isotopic compositions of sediments have long been used to establish trends in past aquatic productivity and water quality (Beeton 1965;Schelske et al 1983;Jeffers et al 2015), but, because of potential taphonomic issues (Anderson 2014;Lu et al 2014) and because these approaches usually do not incorporate consumers, they are unable to measure the direct impacts of anthropogenic nitrogen loading on nutrient dynamics in the wider biotic community (e.g., invertebrates, fish, birds; although for a growing literature on invertebrate analyses, see Perga 2010;Perga et al 2010;van Hardenbroek et al 2010;Frossard et al 2014;Schilder et al 2017;Anas et al 2019). Moreover, while many studies using isotopic analyses of museum-archived vertebrate tissues have been able to make important contributions to understanding how biotic communities have responded to human-caused environmental change during the 20 th century (Fera et al 2017), a lack of suitable specimens from early historical and preindustrial time periods has, in most cases, prevented analyses of longer-term environmental variation in vertebrate taxa (Szpak et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the likely differences in energy and nutrient fluxes through zooplankton taxa with varying dietary niches (Anas et al, 2019;Barnett, Finlay, & Beisner, 2007;Matthews & Mazumder, 2003), we hypothesised that lake/catchment-specific (CHEM + HYDR_LAND) controls of SI composition vary among zooplankton taxa with different dietary niches. Because our previous work (Anas et al, 2014;Scott, Wissel, Gibson, & Birks, 2010) indicated a limited importance of spatial factors in influencing several water chemistry variables (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of their dietary contributions to predators such as fish are often based on SI analyses of carbon and nitrogen (Cabana & Rasmussen, 1994;Persaud & Dillon, 2010;Vander Zanden & Rasmussen, 1999). As mentioned above, among-lake variability in δ 13 C and δ 15 N of these secondary producers can be related to a range of factors associated with energy and nutrient fluxes in lakes, whereas these relations may vary among taxa with different feeding modes and/or habitat specialisations given the likely variations in energy and nutrient pathways through different food-web compartments (Anas et al, 2019;Matthews & Mazumder, 2003;Persaud et al, 2009). For instance, factors controlling primary production can be strongly correlated to δ 13 C variation of selective feeders of phytoplankton relative to non-selective feeders, whereas zooplankton.…”
mentioning
confidence: 99%